Risk in the digital age: Comedian-activists and Trump's cancel culture. (1st June 2021) - Symons, Alex
This article contributes to the study of comedians as activists by examining the campaigns by some of America's most influential figures ‐ Seth Rogan, Jim Carrey, Dave Chapelle, Amy Schumer, Roseanne Barr and Kathy Griffin. To varying degrees, these comedians all use their star images and personal stories to influence public debates through their stand-up, television work, and content on YouTube, Instagram and Twitter. By studying their activities in the media, their press coverage, and public reactions online, this article also presents an original examination of the way 'Cancel Culture' manifests, often hindering their activism. This includes identifying the polarizing influence of the 'Canceller-in-Chief' former president Donald J. Trump, and the risks suffered by comedian-activists in terms of their reputation, commercial prospects, and even their legality. Specifically, this article suggests that 'Cancel Culture' manifests as a spectrum of varying risk which can be shaped by the comedian's star image and the degree of social transgression in their comedy.